2012
DOI: 10.1016/j.fuel.2012.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size and temperature on woody biomass fast pyrolysis at high temperature (1000–1400°C)

Abstract: Effect of particle size and temperature on woody biomass fast pyrolysis at high temperature (1000-1400 degrees C). Fuel, Elsevier, 2012, 97, pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
80
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 20 publications
14
80
1
Order By: Relevance
“…Decarboxylation, depolymerization and thermal cracking reactions are also favoured with the increase in temperature [22]. The slight decrease in gas yield at the highest studied temperature of 1050 °C was most likely due to the series of complex repolymerization and condensation reactions favourable at temperature above 1000 °C [8,23]. These condensation and repolymerization reactions lead to the formation of soot as a significant amount of soot was observed in the system during the 1050 °C experiment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Decarboxylation, depolymerization and thermal cracking reactions are also favoured with the increase in temperature [22]. The slight decrease in gas yield at the highest studied temperature of 1050 °C was most likely due to the series of complex repolymerization and condensation reactions favourable at temperature above 1000 °C [8,23]. These condensation and repolymerization reactions lead to the formation of soot as a significant amount of soot was observed in the system during the 1050 °C experiment.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that above 1000 °C, the tertiary tars (polyaromatic hydrocarbons), acted as a precursor for the formation of soot [32]. These polycyclic aromatic hydrocarbon molecules grow into larger aromatic complexes until they reach a critical mass, forming soot particles [8].…”
Section: Characterization Of Reacted Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental ones are generally performed with lab-scale reactors which allow reproducing some important EFR characteristics as temperature, heat flux, residence time and particle size: the Drop Tube Reactor (DTR). Only few studies have dealt with woody biomass pyrolysis in a DTR above 1000°C [3][4][5][6]. Woody biomass gasification has been studied at high temperature (T > 1000°C) in presence of oxygen [4,7,8] and/or in presence of steam [4,7,[9][10][11] or in presence of carbon dioxide [11].…”
Section: Introductionmentioning
confidence: 99%